Summoning Absent Defendants in Divorce Cases: Fast, Simple, and Low-Cost Justice - Wan Ferry Fadli (Magister Ilmu Hukum Fakultas Hukum Universitas Riau, 2025)
This study analyzes the application of Article 27 of Government Regulation Number 9 of 1975 concerning the Implementation of the Marriage Law related to the procedure for summoning defendants whose whereabouts are unknown in divorce cases in the District Court. This study uses a normative juridical method with a regulatory and conceptual approach to assess its conformity with the principles of simple, swift, and inexpensive justice. The results of the study show that Article 27 normatively serves to maintain legal certainty and prevent the obstruction of judicial proceedings due to the defendant's absence. However, regulations that rely on summonses through conventional mass media reflect a legal framework that is no longer fully relevant to developments in information technology and the digitization of the judiciary. This includes the lengthy summons period, which can take months, slowing down the court proceedings. In the context of modern justice, which is characterized by the implementation of e-Court and e-Litigation systems, a progressive interpretation or regulatory update is needed so that the summons procedure remains effective, efficient, and in line with the principles of access to justice and procedural justice.